Extra-hepatic portal vein obstruction leading to portal cavernoma cholangiopathy without liver dysfunction - Dhanju, Avtar Singh; Narang, Nisha; Singh, Rajdeep; Kaur, Harsimran; Singh, Harkanwarpreet (International Journal of Advances in Medicine, 2023)
In adults, EHPVO mainly occurs following thrombosis, while in children it may be related to congenital malformations and/or neonatal umbilical venous catheterization. EHPVO leads to the cavernous transformation of the portal vein in the absence of recanalization. Portal cholangiopathy (also referred to as portal biliopathy) is common in patients with long-standing chronic PVT. It is due to compression of the large bile ducts by the venous collaterals (portal cavernoma) that form in patients with chronic PVT. Typically, symptoms of portal cholangiopathy include jaundice, biliary colic and pruritus.